THE INFLUENCE OF PRODUCT RATINGS AND SHOPEE CONSUMER REVIEWS ON WARDAH PRODUCT PURCHASE DECISIONS IN BOGOR REGENCY - Nur Fatihah Rizkia; B. Retno Pratiwi Sakti (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of product ratings and consumer reviews on purchasing decisions for Wardah products on the Shopee e-commerce platform in Bogor Regency . The study used a quantitative approach with an associative research type . The research sample consisted of 100 respondents selected using a purposive sampling technique . Data were collected through a Likert- scale -based questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that partially product ratings have a positive and significant effect on purchasing decisions with a calculated t value of 2.260 and a significance of 0.026. Consumer reviews also have a positive and significant effect with a calculated t value of 6.348 and a significance of 0.000, and have a more dominant influence . Simultaneously , product ratings and consumer reviews have a significant effect on purchasing decisions with a calculated F value of 567.534 and a significance of 0.000. The coefficient of determination (R²) value of 0.921 indicates that both independent variables are able to explain 92.1% of the variation in purchasing decisions . This finding confirms that consumer ratings and reviews are important factors in influencing consumer behavior. consumers in the context of online purchasing .